Ethics Management for Supranational Governmental Bodies - Daniela Viviane ABRATZKY; Anna LAŠÁKOVÁ (Communications of International Proceedings, 2021)
This short paper aims at providing an overview of theoretical as well as practical aspects of ethics management, the implementation of ethics and ethics infrastructure elements in public organizations with a focus on supranational governmental bodies. It contrasts the requirements of ethics management for the private versus the public sector in brief. The overview is accompanied by a practical approach, in order to narrow down the observations to concrete aspects of the application of ethics management. The paper specifies findings of important studies of the OECD and the EU Council that clearly focus on implementing ethics management. As a result, several practical recommendations for raising the ethics management effectiveness in supranational public organizations are summarized.
Keywords: Code of Ethics; Ethics Implementation; Ethics Management; EU; OECD; Public Sector; Supranational Governmental Bodies